2010
DOI: 10.2500/ajra.2010.24.3499
|View full text |Cite
|
Sign up to set email alerts
|

Allergic Rhinitis and Inflammatory Airway Disease: Interactions within the Unified Airspace

Abstract: Epidemiological concordance of AR with several airway diseases conforms to a bidirectional "unified airway" respiratory inflammation model based on anatomic and histological upper and lower airway connections. Epidemiology and current understanding of inflammatory, humoral, and neural processes make links between AR and disorders including asthma, otitis media, NP, and CRS plausible. Combining AR with associated conditions increases disease burden; worsened associated illness may accompany worsened AR. AR phar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
71
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(77 citation statements)
references
References 88 publications
(113 reference statements)
1
71
0
5
Order By: Relevance
“…[52][53][54] The eosinophil is drawn to the inflammatory reaction by the T helper 2 (TH2) cytokine interleukin 5 (IL-5). 55 IL-5 mediates eosinophil expansion, priming, recruitment, and prolonged tissue survival in allergic reactions.…”
Section: Inflammatory Mechanismsmentioning
confidence: 99%
“…[52][53][54] The eosinophil is drawn to the inflammatory reaction by the T helper 2 (TH2) cytokine interleukin 5 (IL-5). 55 IL-5 mediates eosinophil expansion, priming, recruitment, and prolonged tissue survival in allergic reactions.…”
Section: Inflammatory Mechanismsmentioning
confidence: 99%
“…We further found that peripheral blood eosinophilia occurred in parallel with tissue eosinophilia and with the erbB1 expression in the nasal gland. The role of eosinophil activation in the pathogenesis of chronic nasal mucosal diseases has been reported in previous studies [19] . Burgel et al [15,20] have documented that activated eosinophils secrete cytokines such as transforming growth factor-␣ and tumor necrosis factor-␣ , which induce the expression of erbB1 on airway epithelial cells.…”
Section: Discussionmentioning
confidence: 99%
“…Although delivery to the nose is optimized with these approaches, subtle effects in the lung, either direct or indirect, cannot be completely discounted. As discussed in the introduction to this chapter, the "united airway" hypothesis linking AR to asthma suggests that immunogenic responses in upper and lower airways are connected (Marple 2010;Pawankar 2006). While asthma:rhinitis relationships are clearly evident in clinical and epidemiological studies, reports from animals models are limited and without a consensus mechanism.…”
Section: Nasal Cavitymentioning
confidence: 99%
“…Given the clinical and pathologic commonalities of AR and asthma, recent efforts of physicians worldwide has led to Allergic Rhinitis and its Impact on Asthma (ARIA), a collaborative development of diagnostic and therapeutic strategies to treat AR as an asthma risk (Bousquet et al 2001). A central tenet of ARIA is that AR and asthma represent a "united airway disease" and should be viewed as an interrelated disease with common etiology, features and treatments (Compalati et al 2010;Marple 2010). However the inherent differences in the anatomic, morphologic, and functional aspects of nasal versus pulmonary airways result in unique inflammatory and allergic responses in each site.…”
Section: Introductionmentioning
confidence: 99%